2011
DOI: 10.1021/ja108516b
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic, Enantioselective Intramolecular [6 + 2] Cycloaddition Reaction for the Formation of Tricyclopentanoids and Insight on Its Mechanism from a Computational Study

Abstract: Diphenylprolinol silyl ether was found to be an effective organocatalyst for promoting the asymmetric, catalytic, intramolecular [6 + 2] cycloaddition reactions of fulvenes substituted at the exocyclic 6-position with a δ-formylalkyl group to afford synthetically useful linear triquinane derivatives in good yields and excellent enantioselectivities. The cis-fused triquinane derivatives were obtained exclusively; the trans-fused isomers were not detected among the reaction products. The intramolecular [6 + 2] c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
55
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 109 publications
0
55
0
1
Order By: Relevance
“…

The first peri-and stereoselective [10+ +4] cycloaddition between catalytically generated amino isobenzofulvenes and electron-deficient dienes is described. [5] Shortly thereafter,organocatalyzed [6+ +2] and [8+ +2] cycloadditions were reported to provide cyclic scaffolds in high enantioselectivities. Experimental and computational investigations support ak inetic distribution of intermediate rotamers dictating the enantioselectivity,w hichr elies heavily on additive effects.

For concise and controlled construction of chiral cyclic structures,c ycloadditions are recognized as highly valuable synthetic strategies.Diels-Alder reactions and dipolar cycloadditions,i nvolving 6p electrons,h ave been particularly useful and am ultitude of enantioselective catalytic versions have been developed.

…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…

The first peri-and stereoselective [10+ +4] cycloaddition between catalytically generated amino isobenzofulvenes and electron-deficient dienes is described. [5] Shortly thereafter,organocatalyzed [6+ +2] and [8+ +2] cycloadditions were reported to provide cyclic scaffolds in high enantioselectivities. Experimental and computational investigations support ak inetic distribution of intermediate rotamers dictating the enantioselectivity,w hichr elies heavily on additive effects.

For concise and controlled construction of chiral cyclic structures,c ycloadditions are recognized as highly valuable synthetic strategies.Diels-Alder reactions and dipolar cycloadditions,i nvolving 6p electrons,h ave been particularly useful and am ultitude of enantioselective catalytic versions have been developed.

…”
mentioning
confidence: 99%
“…[3] Intermolecular higher-order cycloadditions remained elusive in asymmetric catalysis until the first metal-catalyzed [8+ +2] cycloaddition was reported in 2013. [5] Shortly thereafter,organocatalyzed [6+ +2] and [8+ +2] cycloadditions were reported to provide cyclic scaffolds in high enantioselectivities. [5] Shortly thereafter,organocatalyzed [6+ +2] and [8+ +2] cycloadditions were reported to provide cyclic scaffolds in high enantioselectivities.…”
mentioning
confidence: 99%
“…The reaction proceeds well with several substrates, and cis isomers were obtained in every example (Scheme . The proposed reaction mechanism was supported by computational analysis (Scheme 13-13), which showed that the model intermolecular [6þ2] cycloaddition reaction proceeds in a stepwise mechanism via a zwitterionic intermediate [45]. In contrast, the intramolecular [6þ2] cycloaddition leading to the cis-fused linear triquinane skeleton 57 proceeds in a concerted mechanism via a highly asynchronous transition state.…”
Section: [6þ2] Cycloadditionmentioning
confidence: 89%
“…Although a racemic version of this intramolecular [6þ2] cycloaddition reaction (and its reaction mechanism) has been demonstrated by the Houk group [44], an asymmetric catalytic version of this chemistry had not been previously reported. When a linear substrate 53 was exposed to a catalytic amount of 9, a [6þ2] cycloaddition reaction proceeded to afford the tricyclic compound 54 [45]. Two new CÀC bonds are formed in this reaction, via domino enamine/iminium ion intermediates.…”
Section: [6þ2] Cycloadditionmentioning
confidence: 99%
“…[6] Catalytic asymmetric strategies aimed at the analogous spiroindenes are more scarce. [7] We envisioned that organocatalysis [8] could be applied to the stereoselective formation of spiroindenes from benzoful-venes.Astrategy based on trienamine catalysis was chosen, which would grant access to indenes spiro-fused to cyclohexenes by af ormal [4+ +2] cycloaddition (Scheme 1a). [9] The spiroindene products targeted by the envisioned strategy offer an umber of molecular handles for further modifications.Most notably,aMichael acceptor present in the indene ring was demonstrated to facilitate intramolecular cyclizations to yield complex polycyclic products containing as piroindane core.…”
mentioning
confidence: 99%